Difference in leg asymmetry between female collegiate athletes and recreational athletes during drop vertical jump - Morishige, Yutaro (J Orthop Surg Res, 2019)
BACKGROUND: Neuromuscular imbalance will lead to loading asymmetry in sporting activities. This asymmetry is related to leg dominance, which has been associated with increased risk of anterior cruciate ligament (ACL) injury. Therefore, potential biomechanical differences between legs are important. However, little attention has been paid to the biomechanical details of leg dominance. The purpose of the present study was to clarify the relationship between leg dominance and knee biomechanics in females with different activity level during dynamic athletic tasks. METHODS: A total of 23 female collegiate (mean age = 19.6 ± 1.4 years, mean body mass index = 21.5 ± 0.9) and 19 recreational athletes (mean age = 20.7 ± 1.1 years, mean body mass index = 20.5 ± 1.7) were enrolled. Tegner activity scores of the collegiate and recreational athletes were 9 and 7, respectively. Knee kinematic and kinetic asymmetries between the dominant (DL) and non-dominant (NDL) legs during the landing phase of drop vertical jump (DVJ) were assessed using three-dimensional motion analysis in collegiate and recreational athletes separately. Statistical comparison was done using two-tailed paired t test between DL and NDL in each athlete. RESULTS: The peak knee abduction angle was significantly larger on the DL than on the NDL in collegiate athletes. Knee abduction angle at initial contact (IC), peak knee abduction angle, knee internal rotation angle at IC, and peak knee internal rotation angle were significantly larger on the NDL than on the DL in recreational athletes. Moreover, peak knee abduction moment within 40 ms from IC was larger on the NDL than on the DL in recreational athletes, while the moment was not significantly different in collegiate athletes. CONCLUSIONS: From the present study, the relationship between leg dominance and knee biomechanics was totally different in females with different activity level. Specifically, asymmetry of the knee abduction angle between limbs was opposite between female recreational and collegiate athletes. According to previous literatures, abduction and internal rotation angles as well as abduction moment were key issues for mechanism of non-contact ACL injury. Therefore, the NDL in female recreational athletes was associated with increased risk of ACL injury.